Designing a telephone intervention program for family caregivers - Leidy Johanna Rueda Diaz; Diná de Almeida Lopes Monteiro da Cruz (Revista da Escola de Enfermagem da USP, 2018)
ABSTRACT Objective Describing the development process of a nursing intervention program to promote the adaptation of family caregivers for people with chronic diseases in Colombia and Brazil. Method A developmental study in which an intervention program was created as proposed by the UK Medical Research Council for developing and evaluating complex interventions. Results The program was organized into five weekly sessions of 40 minutes duration applied over the telephone, which integrated the activities of Caregiver Support and Improvement in Coping. Conclusion Following the recommendations of the UK Medical Research Council allowed designing an intervention program of high methodological rigor based on existing scientific evidence, and based on a theoretical model from the nursing discipline which will increase the understanding of their mechanisms of action in improving the well-being of family caregivers.